Relationship Between Flow and Athletic Identity: The Case of Three Elite Sportsmen. Issue 2 (3rd April 2017) - Orta, Antonio; Sicilia, Alvaro; Fernández-Balboa, Juan-Miguel
ABSTRACT: This study analyzes the personal narrative of flow experiences across three elite sportsmen within their particular sport autobiographical contexts. Using a holistic formal structure analysis to examine the participants' self-narratives, five major themes emerged: (a) early socialization as the basis of a strong athletic identity, (b) withdrawal from sports as a threat to athletic identity, (c) the dramatic weight of the narrative plots within which the experiences of flow are inserted, (d) biographical sporting flow accounts, and (e) silences and devaluations in flow narrative. The results of the narrative analyses show a close relationship between the flow experiences and athletic identity. This study concludes that, in this case, the narratives of flow experiences have had an ontological role as they served to assert the participants' threatened athletic identity. Hence, studying narratives as practices is a useful way to better understand not only the internal coherence of the narrative fragments into which flow experiences are inserted, but also the role that they play regarding the autobiographical narrative into which these are inserted.